Aplicação de metodologia analítica para a determinação de adultarentes sintéticos em formulações fitoterápicas emagrecedoras no Brasil - Falcão, Tatiana de Mattos (2011)
The problem of adulteration of drugs, nowadays, is not limited just to cases of synthetic formulations (manufactured drugs). The presence of synthetic drugs which are illegally added to herbal formulations, especially those used in the treatment of obesity, is also recurrent. The diet pills called "natural that are the most employeed for this purpose in Brazil are currently the Caralluma Fimbriata, Cascara Sagrada, Vesiculosus Fucus, Centella Asiatica and Garcinia Cambodia. Some synthetic adjuvants are also frequently found in these formulations, such as Vitamin C, collagen and hydrochlorothiazide. This study aimed to analyze samples of herbal in 9 Brazilian states (GO, DF, SC, PR, CE, RJ, RS, SP and MG) in order to detect possible cases of tampering. 106 acquired herbal samples were analyzed using analytical methodology based on capillary zone electrophoresis (CZE) with contactless conductivity detection (C4D). 35.84% of the 106 analyzed samples, showed suspected electrophoretic peaks suspected of tampering with similar characteristics and timing of migration to the contaminants, already studied. 3.8% of the samples by synthetic drugs fenproporex and sibutramine presented adulteration, with concentrations ranging from 3.1 to 10.0 mg / g. The applied methodology allows the identification and quantification of four major adulterants presented in literature (amfepramone, fenproporex, sibutramine and fluoxetine) at concentrations above 1mg / g in weight loss capsules.